Il vocabolario delle reggenze dei nomi italiani - Angelini, Maria Teresa; Fábián, Zsuzsanna (Verbum – Analecta Neolatina, 2003)
In this article, the authors present their new dictionary of the valencies of about 550 Italian nouns, to be published in 2004. The structure of the dictionary is similar to previous Italian-Hungarian valencies dictionaries (published in 1996 and 1998, and also edited by the present authors): the argumental phrases of the selected lemmas (represented by the symbols currently in use in linguistics practice) are accompanied by examples collected from web pages on the Internet.